Orofacial conditions and oral health behavior of young athletes: A comparison of amateur and competitive sports - Merle, C. L.; Richter, L.; Challakh, N.; Haak, R.; Schmalz, G.; Needleman, I.; Wolfarth, B.; Ziebolz, D.; Wüstenfeld, J. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Purpose: This retrospective cross-sectional study aimed to evaluate oral health status (dental, periodontal, and functional) and oral health behavior in young German athletes including the comparison of competitive (CA) and amateur sports (AA). Methods: Data of CA (German national teams, perspective, and youth squads) and AA aged between 18 and 30 years with an available oral examination in 2019 were included. Clinical examination: caries experience (DMF-T), non-carious wear (erosion, BEWE), partially erupted wisdom teeth, gingival inflammation (PBI), plaque index, periodontal screening (PSI), and temporomandibular dysfunction (TMD) screening. Questionnaires: oral health behavior and periodontal symptoms. Results: 88 CA (w = 51%, 20.6 ± 3.5 years) of endurance sports and 57 AA (w = 51%, 22.2 ± 2.1 years) were included. DMF-T was comparable (CA: 2.7 ± 2.2, AA: 2.3 ± 2.2; p = 0.275) with more D-T in CA (0.6 ± 1.0) than AA (0.3 ± 0.7; p = 0.046; caries prevalence: CA: 34%, AA: 19%; p = 0.06). Both groups had low severity of erosion (BEWE about 3.5). CA had more positive TMD screenings (43% vs. 25%; p = 0.014). In both groups, all athletes showed signs of gingival inflammation, but on average of low severity (PBI <1). More CA needed complex periodontal treatment than AA (maximum PSI = 3 in 40% vs. 12%; p < 0.001). Oral health behavior was comparable (daily tooth brushing; regular dental check-ups in >70%). Conclusions: Young German athletes (CA and AA) generally showed signs of gingival inflammation and needed to improve their oral health behavior. CA showed slightly increased oral findings (more D-T, periodontal and TMD screening findings) than AA, but similar oral health behavior. This may imply an increased dental care need in competitive sports.